Anxiety Sensitivity, Fear of Pain and Pain-Related Disability in Children and Adolescents with Chronic Pain - Andrea L Martin; Patricia A McGrath; Stephen C Brown; Joel Katz (Pain Research and Management)
BACKGROUND: Converging lines of evidence suggest that anxiety sensitivity and fear of pain may be important vulnerability factors in the development of avoidance behaviours and disability in adults with chronic pain. However, these factors have not been evaluated in children with chronic pain.